The Bible in the Bowls A Catalogue of Biblical Quotations in Published Jewish Babylonian Aramaic Magic Bowls - Waller, Daniel James (Semitic Languages and Cultures, 2022)
The Bible in the Bowls represents a complete catalogue of Hebrew Bible quotations found in the published corpus of Jewish Babylonian Aramaic magic bowls. As our only direct epigraphic witnesses to the Hebrew Bible from late antique Babylonia, the bowls are uniquely placed to contribute to research on the (oral) transmission of the biblical text in late antiquity; the pre-Masoretic Babylonian vocalisation tradition; the formation of the liturgy and the early development of the Jewish prayer book; the social locations of biblical knowledge in late antique Babylonia and socio-religious typologies of the bowls; and the dynamics of scriptural citation in ancient Jewish magic. In a number of cases, the bowls also contain the earliest attestations of biblical verses not found in the Dead Sea Scrolls. Pre-dating the next available evidence by four to five centuries, the bowls are a valuable resource for biblical text critics. By making these valuable witnesses to the Hebrew Bible easily available to scholars, The Bible in the Bowls is designed to facilitate further research by linguists, liturgists, biblical text critics, and students of Jewish magic. It collates and transcribes each biblical verse as it appears in the published bowls, furnishes details of the bowls' publication, and notes various features of interest. The catalogue is also accompanied by an accessible introduction that briefly introduces the incantation bowls, surveys their deployment of scripture in light of their magical goals, and discusses the orthography of the quotations and what this can tell us about the encounter with the biblical text in late antique Babylonia.